Exercise levels and preferences on exercise counselling and programming among older cancer survivors: A mixed-methods study. Issue 8 (November 2021) - Cheung, Denise Shuk Ting; Takemura, Naomi; Chau, Pui Hing; Ng, Alina Yee Man; Xu, Xinyi; Lin, Chia Chin
Abstract: Objectives: To assess exercise levels and exercise counselling /programming preferences among older cancer survivors. Materials and methods: A mixed-methods study design was employed. Quantitative instruments on exercise levels, exercise counselling and programming preferences, frailty status, and cancer-related symptoms were administered to 290 post-treatment older cancer survivors aged ≥65. Twelve participants with different exercise levels and different views on exercise counselling and programming were purposively selected to participate in semi-structured interviews. Results: Overall, 58.3% of participants did not meet the recommended exercise guidelines, and 44.1% were not engaging in any vigorous or moderate exercise. Frail survivors were less likely to meet the guidelines (aOR = 0.194, 95%CI = 0.053, 0.712) compared to their robust counterparts. However, 66.9% and 62.8% of participants expressed a definite or possible interest in receiving exercise counselling and participating in an exercise program, respectively. Particularly, survivors who are male, did not receive chemotherapy, are less educated, and have higher symptom burden were less likely to show interest. Most preferred low-intensity exercise (59.8%) and wanted to start the exercise program after treatment (68.2%), which differs from the literature on general adult survivors. The major trigger to initiate and maintain exercise behaviors was the benefits of exercise and a common barrier to exercising was lack of time. Conclusion: Most older cancer survivors did not meet the recommended exercise guidelines, but they were open to exercise counselling and programming. Reviewing education on the benefits of exercise is especially important after treatment completion to promote healthy lifestyles.